To fill in the missing values in the table using the equation y-3=-2x, we can substitute the given x-values into the equation to solve for the corresponding y-values.
Given equation: y-3=-2x
Plugging in x = 0:
y - 3 = -2(0)
y - 3 = 0
y = 3
Plugging in x = 1:
y - 3 = -2(1)
y - 3 = -2
y = 1
Plugging in x = -2:
y - 3 = -2(-2)
y - 3 = 4
y = 7
Plugging in x = -3:
y - 3 = -2(-3)
y - 3 = 6
y = 9
Plugging in x = 5:
y - 3 = -2(5)
y - 3 = -10
y = -7
The completed table would look like this:
x | y
-------
0 | 3
1 | 1
-2 | 7
-3 | 9
5 | -7
Use the equation y-3=-2x to fill in the missing values in the table
1 answer